P5 Module Embedded System online training using HD-2020 for vocational students in Surabaya - Heny Yuniarti; Reni Soelistijorini; Maretha Ruswiansari; Setiawardhana Setiawardhana; Riyanto Sigit; Bayu Sandi Marta; Mochamad Mobed Bachtiar; Dewi Mutiara Sari; Iwan Kurnianto Wibowo (University of Merdeka Malang, 2022)
Vocational students need hard skills and empowerment to enter the workforce. This community service activity aims to improve the skills of SMK Negeri 6 Surabaya students through training to make simple applications for running text LEDs from the P5 module. Running text is one of the electronic media that is very useful for conveying messages and information. Program activities that have been adapted to the needs of the school. So that this program is able to improve the quality of their hard skills and bring benefits to the community, lecturers, employees, and students of the EEPIS (Electronic Engineering Polytechnic Institute of Surabaya) Computer Engineering Study Program. The implementation method includes an initial survey of partner needs, vocational needs analysis, online training preparation, and installation and delivery of tools. The results of the post-test using a questionnaire showed that 97.9% of participants stated that there was an increase in embedded systems skills, especially in the P5 module and its software applications. There were 85.4% of participants wanted to learn more about embedded systems for other areas of expertise.